2021
DOI: 10.1073/pnas.2021998118
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin-binding domain of Ki-67 together with p53 protects human chromosomes from mitotic damage

Abstract: Vertebrate mammals express a protein called Ki-67 which is most widely known as a clinically useful marker of highly proliferative cells. Previous studies of human cells indicated that acute depletion of Ki-67 can elicit a delay at the G1/S boundary of the cell cycle, dependent on induction of the checkpoint protein p21. Consistent with those observations, we show here that acute Ki-67 depletion causes hallmarks of DNA damage, and the damage occurs even in the absence of checkpoint signaling. This damage is no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
(114 reference statements)
2
4
0
Order By: Relevance
“…We cannot link these genes to initial Ki-67 binding or Ki-67 biology. A similar result was obtained in a recent study that also employed auxin-mediated Ki-67-AID depletion in HCT116 cells (Garwain et al , 2020).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We cannot link these genes to initial Ki-67 binding or Ki-67 biology. A similar result was obtained in a recent study that also employed auxin-mediated Ki-67-AID depletion in HCT116 cells (Garwain et al , 2020).…”
Section: Resultssupporting
confidence: 89%
“…We then asked whether Ki-67 contributes directly to the transcriptional repression of these genes. Several studies have found changes in gene activity upon Ki-67 loss (Garwain et al , 2020; Mrouj et al , 2021; Sobecki et al , 2016; Sun et al , 2017), but none could attribute this to direct effects, in part because the binding pattern of Ki-67 was not known. We therefore generated RNA-seq data in the HCT116 Ki-67-AID cells.…”
Section: Resultsmentioning
confidence: 99%
“…We cannot link these genes to initial Ki‐67 binding or Ki‐67 biology. A similar result was obtained in a recent study that also employed auxin‐mediated Ki‐67‐AID depletion in HCT116 cells (Garwain et al , 2020).…”
Section: Resultssupporting
confidence: 87%
“…We then asked whether Ki‐67 contributes directly to the transcriptional repression of these genes. Several studies have found changes in gene activity upon Ki‐67 loss (Sobecki et al , 2016; Sun et al , 2017; Garwain et al , 2020; Mrouj et al , 2021), but none could attribute this to direct effects, in part because the binding pattern of Ki‐67 was not known. We therefore generated RNA‐seq data in the HCT116 Ki‐67‐AID cells.…”
Section: Resultsmentioning
confidence: 99%
“…In our post‐traumatic rabbit TMJ OA model, our RNA‐seq analyses reveal for the first time changes in gene expression levels of cell cycle process within each tissue group. Upon further investigation, we found that genes related to the cell cycle process were downregulated in the injured SZ group relative to healthy SZ tissues, including MKI67 28,29 and PCNA 30 . On the other hand, genes related to cell cycle were significantly upregulated in the injured CC group compared to healthy CC group (Figure 6A).…”
Section: Resultsmentioning
confidence: 95%